The Right to Die: Legalizing Medical Assistance in Dying in Canada - Noushon Farmanara (McMaster University Library Press, 2017)
Permitting medical assistance in dying has been a contentiously debated issue in Canada for decades. In June of 2016, the federal government passed legislation that amended the Criminal Code to permit eligible adults to request and receive medical assistance in dying (MAiD). Two major Supreme Court cases challenged the prohibition of MAiD, with very different results. Although the cases of Rodriguez vs. British Columbia and Carter vs. Canada were strikingly similar, a shifting political, social, and international landscape over the two decades between the two cases produced very different outcomes. The 2015 landmark decision in Carter vs. Canada thrust the issue of MAiD onto the federal government's agenda. While federal legislation was enacted, the provision of MAiD falls to the responsibility of provinces and territories. Ensuring that the practice is properly implemented, monitored, and regulated will be a pressing challenge moving forward.